THE DRIVERS OF FIRM VALUE - Rahayu Lestari; Suadi Sapta Putra; Elwisam; Kumba Digdowiseiso; Rohana Ahmad (RADJA PUBLIKA, 2024)
The objective of this literature review is to identify and analyze the factors that determine the value of a company, as evidenced in multiple studies. This study focuses on comprehending the determinants that impact the evaluation of a company's worth, a significant subject in the field of economics and finance. The chosen approach is Systematic Literature Review (SLR), which involves gathering and assessing relevant literature pertaining to the research topic. The results of the Systematic Literature Review (SLR) analysis indicate that financial performance, institutional ownership, capital structure, company size, corporate governance, corporate social responsibility, and dividend policy are the primary determinants of company value. The discussion emphasizes the discrepancies in research findings and contextual disparities that can influence the connection between determinants and firm value. While these findings offer a more profound comprehension of the intricate factors that influence firm value assessments, additional research is required to elucidate the precise impacts and identify particular market situations that moderate this relationship. The findings of this literature review emphasize the significance of considering multiple factors in order to comprehensively comprehend the overall value of a firm. Additionally, it highlights the need for future research to delve into the dynamics of the relationship between these factors and firm value.